Levels of physical dependence on tobacco among adolescent smokers in Cyprus - Christophi, Costas A.; Pampaka, Despina; Paisi, Martha; Ioannou, Solonas; DiFranza, Joseph R. (My University, 2016)
Purpose: The purpose of this study is to assess tobacco dependence among Cypriot adolescents and examine its association to cigarette consumption and attitudes towards smoking. Methods: The current study used cross-sectional data from the 2011 Cyprus Global Youth Tobacco Survey which adopted multistage cluster sampling methods to select adolescents registered in middle and high schools in Cyprus. Tobacco use, physical dependence on tobacco, and attitudes towards tobacco use were measured in 187 adolescents aged 13-18 years old who reported that they had smoked at least once in the preceding 30 days. Physical dependence was assessed using the Levels of Physical Dependence scale. Results: Physical dependence was present in 86% of the adolescent smokers. The mean latency to needing among smokers in the highest dependence group was 101 h. Significant associations were observed between physical dependence and the perceived difficulty in quitting (OR = 13.1, 95% CI: 4.0, 43.0) as well as the expectation to continue smoking for the next five years (OR = 3.3, 95% CI: 1.3, 8.4). Significant associations were also observed between physical dependence and the number of smoking days per month, daily smoking, daily cigarette consumption, lifetime cigarette consumption, and perceived difficulty in abstaining from smoking for one week. Conclusions: Physical dependence provides a symptom-based approach to assess dependence and it is a strong predictor of adolescents' perceptions of their ability to quit or to refrain from smoking for a week. Physical dependence on tobacco was highly prevalent among adolescent smokers in Cyprus and it was associated with greater perceived difficulty in quitting. Interventions targeting adolescent smoking must account for the high prevalence of physical dependence.
Keywords: Addiction; Cyprus adolescents; Latency; Physical dependence; Smoking; Tobacco dependence